Prakriti in Siddha Medical System - A Review - Thayalini, T.; Vidhya Milano, P. (Bandaranaike Memorial Ayurvedic Research Institute Navinna, Maharagama, 2015)
Prakriti is mentioned in different Siddha text books under different terms such as dehakkooru, sareerakkooru, Udambukaliniyatkaikunam, Yakkayinillakkanam, dehalakshanm, and dehakuri. In Ayurveda it is mentioned as Prakriti. It is recorded that as "due to food habits, the dosha which increases during the fertilization of sperm and ovum, is the main reason for the formation of Yakkai, and the body is called accordingly. The body which forms with more vali, alal and iyam called as valiudal/vathadeham, alaludal/alaldeham and iyaudal/ kaphadeham respectively. Types of prakriti are mentioned as vathadeham, pithadeham and kaphadeham and vathadehilakshanam, pithadehilakshanam and sileshmadehilakshanam. These three doshas are very important in the treatment of disease in Siddha system of medicine. Diagnosis in Siddha system of medicine cannot be completed without defining the constitution of an individual. Because treatment differs according to Prakriti (Dehakooru) of an individual. Siddha believes that medicine is for an individual person but not for an individual organ or system. In order to get a clear picture of dehakooru, referring nine different books prepared the review. Most of the Siddha text books mention prakriti in same manner but there are some variations in the book sihitcharathnatheepam.
Keywords: Alaldeham; Iyadeham; Valideham; Yakkai